Production of β-galactosidase by Trichoderma reesei FTKO-39 in wheat bran: Partial purification of two isozymes - Adalberto, P. R.; Massabni, A. C.; Goulart, A. J.; Contiero, J.; Carmona, E. C.; Cardello, L.; Monti, R. (My University, 2006)
Trichoderma reesei FTKO-39 grown at 35°C for 5 d on wheat bran supplemented with MgCl2 and lactose as the carbon source produced two isozymes of β-galactosidase: BGT I and BGT II. These isozymes were partially purified on a DEAE-Trisacryl column. Both BGT I and BGT II fractions exhibited optimum activity at 65°C, but the pH optima were 4.0 and 6.5, respectively. The isozymes also showed similar thermal stability. However, BGT I was more stable than BGT II in a pH range of 3.0-10.0. At least two different β-galactosidases are produced by T. reesei, as revealed by the two bands seen on a 6% polyacrylamide gel stained for activity. Copyright © 2006 by Humana Press Inc. All rights of any nature whatsoever reserved.
Keywords: β-Galactosidase; Isozymes; Partial purification; Semisolid fermentation; Trichoderma reesei